The communion of women missions and gender in colonial Africa and the British metropole - Prevost, Elizabeth E. (Oxford University Press, 2010)
Elizabeth Prevost examines the massive Protestant campaign of female missionary expansion between the 1860s and 1930s, through a comparison of Anglican women's experience in Uganda and Madagascar.